Analisis Pengaruh Variabel Pengetahuan Lokasi Dan Lingkungan Sosial Terhadap Minat Santri Pada Bank Syariah - Amiruddin, M.; Budianto, Eka Wahyu Hestya (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2025)
The main objective of this study is to reveal the factors that play a role in the savings habits of Islamic boarding school students, especially in the context of Islamic banking. This study focused on students of the Sabilurrosyad Gasek Islamic Boarding School in Malang, with all 81 students who had filled out the questionnaire as the population and sample. Statistical analysis shows that students' knowledge of Islamic banking products and principles has a significant impact on their tendency to save in Islamic banks. However, the social environment does not have a significant effect on their savings behavior, nor does the location or distance of the Islamic bank from the Islamic boarding school.